The relationship between emotional intelligence and adjustment amongst first year students in a Malaysian Public University - Chong Abdullah, Maria; Elias, Habibah; Mahyuddin, Rahil; Uli, Jegak (The International Journal of Interdisciplinary Social Sciences, 2009)
This study aimed to investigate the relationship between emotional intelligence (EI) and university adjustment and academic achievement of 250 first year students attending various undergraduate programs at a Malaysian public university. The study employed a correlation design and data was analyzed using descriptive and inferential statistics to address the research objectives. Findings from this study showed that there is significant and positive relationship between students’ EI and their overall university adjustment, academic adjustment, social adjustment, personal-emotional adjustment, students’ attachment to university, and academic achievement. Results also indicated that throughout a period of one semester, students’ overall adjustment and academic achievement was found to be significantly predicted by their EI .